Crosstalk between the gut microbiota and brain network topology in poststroke aphasia patients: perspectives from neuroimaging findings - Yun Cao; Jiaqin Huang; Danli Zhang; Jianguang Ji; Xiaojing Lei; Zhongjian Tan; Jingling Chang (Therapeutic Advances in Neurological Disorders)
Background: Emerging evidence indicates that gut inflammatory and immune response play a key role in the pathophysiology of stroke and may become a promising therapeutic target. However, the specific role of the microbiota-gut-brain axis in poststroke aphasia (PSA) patients remains unclear. Objectives: The aim of this study was to investigate the relationships among the gut microbiota, neuroendocrine-immune network, brain network properties, and language function in patients with PSA. Design: This is a cross-sectional, observational, monocentric study. Methods: This study enrolled 15 PSA patients, 10 non-PSA patients, and 15 healthy controls (HCs). All subjects underwent stool microbiota analysis, blood inflammatory cytokines assessment, and brain-gut peptide examination. PSA patients and HCs underwent additional resting-state functional MRI (rs-fMRI) brain scans. The rs-fMRI data were utilized to create whole-brain connectivity maps, and graph theory was employed to characterize the network topological properties. Analysis of variance and the Kruskal–Wallis test were used for comparisons among the three groups. Correlation analyses were subsequently conducted to explore relationships among factors showing significant group differences. Results: Compared with non-PSA patients and HCs, PSA patients displayed alterations in the gut microbiota composition, increased systemic inflammation, changes in brain-gut peptides, and had worse language performance. Graph theoretical analysis revealed that PSA patients exhibited small-world topology. Furthermore, nodal measures in brain network analysis showed activation of homologous speech areas in the right hemisphere, while the nodal properties of brain regions near the lesion in the left hemisphere decreased in patients with PSA compared with HCs. Conclusion: The present study revealed, for the first time, that an imbalance in gut microbiota was accompanied by the neuroendocrine-immune network disorder and abnormal changes in the brain network in PSA patients.